Best Answer

We can solve this system of equations by subtracting the second equation from the first:

5x + 3y = 26

-2x + 7y = 6

7x + 4y = 20

Now we can divide both sides by 4 to isolate the y-term:

7x + 4y = 20

4 4 4

7x/4 + y = 5

Now we can subtract 7x/4 from both sides to isolate the x-term:

7x/4 + y = 5

-7x/4 -7x/4

y = 5 - 7x/4

Plugging this back into the first equation and simplifying, we have:

5x + 3(5 - 7x/4) = 26

5x + 15 - 21x/4 = 26

-16x/4 = 11

x = -11/16

Plugging this back into the equation for y, we have:

y = 5 - 7x/4 = 5 - 7(-11/16)/4 = 5 + 33/16

Therefore, the solution to the system is x = -11/16 and y = 33/16.

Q: 5x+3y=26-2x+7y=6

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Related questions